علاقة الذكاء الجسمي الحركي بأداء بعض المهارات الهجومية في كرة اليد - قعقاع, توفيق (جامعة الوادي - University of Eloued, 2021)
هدفت الدراسة الى معرفة مدى مساهمة الذكاء الجسمي الحركي في اداء بعض المهارات الهجومية في كرة اليد، حيث استخدم الباحث المنهج الوصفي الارتباطي لملائمة طبيعة الدراسة، واشتملت عينة الدراسة (20) لاعبا فئة الاقل من 17 سنة من لاعبي كرة اليد (JSBM) الناشط في القسم الهواة بالطريقة العشوائية، وقد استنتج الباحث بأن هناك علاقة ذات دلالة احصائية بين متغيرات الدراسة (الذكاء الجسمي الحركي وجملة من المهارات الهجومية في كرة اليد)، ويوصي الباحث بضرورة تطبيق انواع المقاييس الخاصة بالذكاء (سواء الانفعالي، العاطفي، الاستراتيجي) او الذكاء الجسمي الحركي لما له اهمية كبيرة في التعرف على السلوك الداخلي للاعب، وتوظيف دراسات مشابهة في ما يخص مقاييس الذكاء في شتى الجوانب، وضرورة الاهتمام بمتغير الذكاء الجسمي الحركي وتطويره. الكلمات المفتاح: الذكاء الجسمي الحركي، المهارات الهجومية، كرة اليد. Abstract: The study aimed to find out the extent of the contribution of body-kinetic intelligence to the performance of some offensive skills in handball, where the researcher used the descriptive approach to suit the nature of the study, and the study sample included (20) players of the category of less than 17 years of handball players (JSBM) active in the amateur section By the random method, the researcher concluded that there is a statistically significant relationship between the study variables (body-kinesthetic intelligence and a group of offensive skills in handball), and the researcher recommends the necessity of applying the types of measures of intelligence (whether emotional, emotional, strategic) or physical-kinesthetic intelligence because of its Of great importance in identifying the internal behavior of the player, and employing similar studies regarding measures of intelligence in various aspects, and the need to pay attention to and develop the physical intelligence variable.
The relationship of the body-kinesthetic intelligence to the performance of some offensive skills in handball
مقال
Keywords: الذكاء الجسمي الحركي ، المهارات الهجومية ، كرة اليد; body kinesthetic intelligence, offensive skills, handb